Propagation of weak shock waves in non-uniform, radiative magnetogasdynamics - Singh L.P.; Ram S.D.; Singh D.B. (My University, 2025)
A problem of propagation of weak planer shock wave in radiative magnetogasdynamics is theoretically investigated. The gas is taken to be sufficiently hot for the effects of thermal radiation to be significant, which are of course treated by the optically thin approximation to the radiative transfer equation. The density of the medium ahead of the shock wave is assumed to be exponentially varying. A systematic perturbation scheme is used to obtain the analytical solution of the flow field. Also, an approximate solution near the front shock is determined. The effect of radiation and magnetic field strength on the shock wave propagation is examined. © 2010 Elsevier Ltd. All rights reserved.